Causality between Selected Energy Companies’ Price Indexes and Barel Oil Prices - Huseynli, Nigar (International Journal of Energy Economics and Policy, 2023)
Energy production and consumption have an important place in the world. Due to the increase in demand, it reveals the result of the valuation of the companies in this sector. The main purpose of this study is to analyze the relationship between brent oil prices in the world and the index prices of energy companies, which are among the world’s most important and top 10 companies. The research covers the period between January 2011 and July 2022. The time series was created by considering the data in the selected time period on a monthly basis. Co-integration analysis was applied to the series and the relationship between the variables was tried to be determined. Short-term relationships were examined by applying the VAR model. At this stage, causality was carried out with Granger causality analysis. As a result of the analysis, it was concluded that brent oil prices, which were formed as a result of events in the world, had an effect on the index prices of two important energy companies, Exxon Mobile and Gazprom. In other words, there is a causal relationship between these variables. This bilateral causality relationship between Brent oil prices and Exxon Mobile is realized unilaterally with the other two energy companies. In short, there is a Granger causality relationship between these variables.